Three new Helicopsyche from Laos (Trichoptera: Helicopsychidae) - Johanson, Kjell Arne; Malm, Tobias (Zootaxa, 2007)
Three new species, Helicopsyche pathoumthongi, Helicopsyche vongsombathi, and Helicopsyche laoensis, are described and illustrated based on material collected in northern Laos from April–May, 2005. With Helicopsyche antikleia Malicky, 1997, originally described from Laos, and the discovery of a single male of the widespread Oriental species Helicopsyche angusta (Ulmer, 1951) the Laotian Helicopsyche fauna now contains 5 recorded species.